1988
DOI: 10.1080/00140138808966676
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of human palmar skin friction and the effects of materials, pinch force and moisture

Abstract: A study was conducted to determine the friction characteristics for various materials against human palmar skin. Seven materials were tested using two pinchforce levels under both moist and dry conditions. Using a two-fingered pinch grip, subjects held a specially designed dynamometer covered with one of the test materials. They maintained a constant pinch force as load force was increased at a constant rate until the dynamometer slipped from their fingers. The load force at the slip point was then used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 6 publications
5
67
1
1
Order By: Relevance
“…For textures which have very small surface areas in contact with the skin, or where there is sufficient moisture to form a lubricating boundary layer between the skin and the surface, the coefficient of friction will be reduced (Comaish and Bottoms 1971;Highley et al 1977;Nacht et al 1981). However, most studies of moisture on the skin indicate that hydration of the cells of the stratum corneum substantially increases skin adhesiveness to most surfaces (Cussler et al 1977;Highley et al 1977;Wolfram 1983;Gerrard 1987;Buchholz et al 1988). The data from the present study suggest that, in general, subjects are able to detect and compensate for losses in skin friction due to changes in the intrinsic mechanical properties of the skin itself.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…For textures which have very small surface areas in contact with the skin, or where there is sufficient moisture to form a lubricating boundary layer between the skin and the surface, the coefficient of friction will be reduced (Comaish and Bottoms 1971;Highley et al 1977;Nacht et al 1981). However, most studies of moisture on the skin indicate that hydration of the cells of the stratum corneum substantially increases skin adhesiveness to most surfaces (Cussler et al 1977;Highley et al 1977;Wolfram 1983;Gerrard 1987;Buchholz et al 1988). The data from the present study suggest that, in general, subjects are able to detect and compensate for losses in skin friction due to changes in the intrinsic mechanical properties of the skin itself.…”
Section: Discussionsupporting
confidence: 53%
“…Altering the friction of the skin has also been the subject of extensive study by the cosmetic industry, and these investigations have clearly demonstrated that moisture, and in particular sweat, can increase skin friction (Cussler et al 1977;Highley et al 1977;Wolfram 1983;Gerrard 1987;Buchholz et al 1988). Gerrard (1987 found that water alone increased the friction of skin on smooth steel from 0.20 to 0.70.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory information signalling object weight and surface texture is also used to economically scale fingertip forces during dynamic manipulation of a hand-held object. Sensory feedback is used to update the internal neural representation of the physical object properties, such as weight, surface texture and shape (Buchholz et al 1988;Cadoret and Smith 1996;Johansson and Westling 1984), gained during prior manipulative experience with similar objects. Recently, we demonstrated that the absence of sensory feedback from the grasping digits during digit anaesthesia results in an uneconomical increase of grip forces during arm movements with a grasped object (Nowak et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…First, friction is the force that enables man to work with objects in his environment, which, with out friction, would slip through his fingers. The occupa tional dermatologist may assist in the design of tools by advising on optimal skin-tool interfaces (1,2]. Secondly, cosmetic products may influence tactile skin properties (smoothness, greasiness), which correspond to frictional properties.…”
Section: Introductionmentioning
confidence: 99%